Does short-term endotracheal intubation affects the acoustic characteristics? - Toran, KC; Lal, BK (Kathmandu University Medical Journal, 2010)
Introduction: Endotracheal intubation can produce various degrees of temporary and sometimes permanent damage to the laryngotracheal mechanism. Recent development of computer based voice analysis technology can now detect a minute changes in acoustic waveforms which a normal human ear cannot. In the study we compared and analyzed the acoustic waveforms of 35 patients undergoing surgery under intubation anaesthesia. Objective: The aim of the present series is to analyze the effects of short term intubation with computerized voice laboratory. Materials and methods: Values of acoustic waveforms obtained from 35 patients were compared 48 hours after the short term endotracheal intubation anaesthesia. The comparisons were made in terms of perturbation (jitter and shimmer), harmonic- to noise ratio (HNR) and fundamental frequency (F0). Results: The pre-intubated voice characteristics when compared with the post-intubation group did not reveal any statistical difference (P>0.05). However, there was only a minimal decrease in F0. Conclusion: The study revealed that, short term intubation anaesthesia does not alter the acoustic characteristics. The analysis of acoustic waveforms is a non invasive technique that helps to evaluate the effects of tracheal intubation on laryngeal function, a technique that warrants further evaluation. Key words: Acoustic characteristics; Endotracheal intubation; Voice DOI: 10.3126/kumj.v8i1.3219 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 35-39